Análise da viabilidade da instalação de um grupo gerador em uma indústria para suprir a demanda em horários de ponta e/ou emergência - Marcante, Luan Ruaro (2011)
This research is the development of an analysis of the possibility of reducing the energy bill and a method to analyze the economic feasibility of installing a generator in an industry. It also proposed a review of concepts related to power generation in peak hours and emergency and the way in which a correct administration of the electrical energy consumption affects the reduction of power tariff setting. In an industry, an interruption in electricity supply by the concessionaire could result in the loss of productivity. Thus, the use of generators as an alternative to meet the power supply, both in peak and in emergency can mean a reduction in electricity tariff for greater safety in production processes. A considerable reduction in the cost of electricity can be combined with an initial investment in a generating station from diesel, which has been widely used for reasons of reliability and economy. Thus, this work presents a proposal for analyzing the feasibility of installing a generator, the company Hi-Mix Eletrônicos, considering its use during peak hours, where the pricing is higher, within a display report that discloses the reduction of the energy bill of the company, resulting in reduced production costs.